Post-Anthropocentric Land Law: Reconstruction of Agrarian Legal Philosophy Based on Ecological Justice in Indonesia - Sinung Mufti Hangabei; Eldi Nasali; Hengky Afandi (Indonesian Journal of Law and Policy Studies, 2023)
Agrarian law in Indonesia has long been influenced by an anthropocentric paradigm that places humans as the central focus in land governance. This perspective often prioritizes economic exploitation of land while neglecting its ecological functions, which contributes to environmental degradation, ecological imbalance, and conflicts over land use.This study aims to reconstruct the philosophical foundation of agrarian law in Indonesia by introducing a post-anthropocentric perspective based on the principle of ecological justice, in order to create a more balanced and sustainable land governance system.The research uses a normative juridical method with a philosophical and conceptual approach. It examines legal doctrines, legislation, and theoretical perspectives related to agrarian law, ecological justice, and environmental philosophy to analyze the need for reconstructing the existing legal paradigm.The study finds that the current agrarian legal framework still largely reflects anthropocentric values, which limit the protection of ecological interests. Integrating ecological justice principles into agrarian law can strengthen the recognition of land’s ecological, social, and sustainability functions while promoting more responsible and balanced land management.The novelty of this research lies in proposing a reconstruction of Indonesia’s agrarian legal philosophy through a post-anthropocentric approach that places ecological justice as a fundamental principle in land governance and legal development